Forming Olivine Phenocrysts in Basalt: A 3D Characterization of Growth Rates in Laboratory Experiments - Mourey, Adrien J.; Shea, Thomas (Frontiers in Earth Science, 2019)
Our current knowledge of the genesis, ascent, storage, and eruption of mafic magmas is intimately linked with olivine, its primary crystal cargo. Recent claims that phenocryst-size crystals can grow rapidly and non-concentrically are challenging our perception of what olivine zoning represents (e.g., controlled by growth and/or diffusion), and whether accurate magma crystallization and diffusion timescales can be retrieved. A series of cooling experiments using a dry basalt was carried out in order to quantify the kinetics of olivine growth as a function of the degree of undercooling, and to characterize morphological changes occurring with time. After a 24 h equilibration step at 1290°C (10°C above the olivine liquidus), experiments were rapidly cooled to final temperatures Tf = 1270, 1255, 1240, or 1220°C (imposing undercoolings of −ΔT = 10, 25, 40, and 60°C, respectively). Growth rates estimated via 3D microtomography renderings of experimental crystals attain 10–7 m/s, and are found to be almost an order of magnitude higher than those calculated using 2D sections of the same experiments. We show that mm-sized crystals similar to those found in natural Kīlauea samples can be produced after a few hours under moderate undercooling conditions (25–60°C). Growth rates decrease faintly with time, accompanying transitions between skeletal/hopper and more polyhedral morphologies. Growth rates generally increase until −ΔT = 40°C, and decrease slightly at −ΔT = 60°C as rates of nucleation likely increase. The −ΔT = 40°C vicinity may therefore represent a thermal “sweet spot” for the formation of phenocrysts in dry basalt. Olivine overgrowths on crystals that survived initial dissolution grow slower than homogeneously nucleated crystals, illustrating how new and old crystals in natural magmas likely respond differently to a thermal perturbation. We suggest that the main growth direction of natural olivine (a- or c-axis) may be a sensitive function of undercooling and the presence of a pre-existing growth substrate. Olivine grows faster along the a-axis under moderate to high undercooling conditions, while preferred development along the c-axis likely occurs under lower undercooling conditions and/or as rims grow around existing crystals. The early history of skeletal olivine crystals is controlled by diffusion in the melt (diffusion-controlled growth regime), while their long-term compositional zoning history is mainly controlled by diffusive re-equilibration.